Разработка требований по биологической защите операторов портативных свч средств функционального подавления с фокусировкой ЭМИ в ФАР - Преснякова, А. Д.; Дзюбан, В. Н. (ХНУРЕ, 2019)
Developed requirements for the biological protection of operators portable microwave means of functional suppression with electromagnetic radiation focusing in phased antenna arrays.